2023
DOI: 10.17556/erziefd.1111846
|View full text |Cite
|
Sign up to set email alerts
|

Ebeveynlerin Gözünden Çocuklarının Dijital Oyun Oynama Alışkanlıklarının Değerlendirilmesi

Abstract: Bu çalışmanın amacı 0-8 yaş arasında çocuğu olan ebeveynlere göre çocuklarının dijital oyun oynamaya başlama süreçleri, dijital oyun kullanım durumları ve bu oyunların çocuklar üzerindeki etkisinin belirlenmesidir. Karma araştırma yöntemlerinden yakınsayan paralel desenin kullanıldığı bu çalışmada verilerin toplanmasında Erken Yaşlarda Dijital Oyunların Etkileri Ölçeği, Problemli Medya Kullanım Ölçeği ve yarı yapılandırılmış görüşme soruları kullanılmıştır. Çalışmanın nicel kısmında 387 ebeveyne ölçek uygulanm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This study provides detailed knowledge about the preferences of children with special needs regarding on digital games. When the literature was examined, many studies on children with typical development and their parents were found (Eryol, 2023;Ferguson, 2015;İnce, 2022;Jones, 2014;Lemmens et al, 2011;Mercan-Uzun et al, 2023;Smith, 2010;Sönmez & Sönmez, 2023;Swing et al, 2010;Toran et al, 2016;Üstündağ, 2019). However, studies investigating the effects of digital games on children with special needs are quite limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This study provides detailed knowledge about the preferences of children with special needs regarding on digital games. When the literature was examined, many studies on children with typical development and their parents were found (Eryol, 2023;Ferguson, 2015;İnce, 2022;Jones, 2014;Lemmens et al, 2011;Mercan-Uzun et al, 2023;Smith, 2010;Sönmez & Sönmez, 2023;Swing et al, 2010;Toran et al, 2016;Üstündağ, 2019). However, studies investigating the effects of digital games on children with special needs are quite limited.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Today, in parallel with technological developments, children's games and play tools, even playgrounds, have changed and the concept of digital games has emerged and taken place in children's lives (Bird & Edwards, 2015;Gözüm & Kandır, 2020a;İnan & Dervent, 2016). In studies on the concept of digital games, which have increased in recent years, the frequency of children playing digital games (Akçay & Özcebe, 2012;Gözüm & Kandır, 2021;Işıkoğlu-Erdoğan, 2019;), game preferences (Tuğrul et al, 2014), game addiction (Ünsal, 2019), parents' views (Gözüm, 2022;Işıkoğlu-Erdoğan et al, 2019;Mercan-Uzun, Bütün-Kar & Özdemir, 2023;Yiğit & Alat, 2022), the effects of digital tools and games on their children's development (Gözüm & Kandır, 2020b;Taş & Güneş, 2019;Toksoy, 2018) are included. When these studies are examined, it is seen that the number of studies with children in the early childhood period is very limited and the study group of the studies generally consists of children aged six and over.…”
Section: Introductionmentioning
confidence: 99%